The Impact of Zinc Supplementation on the Course of Infections - Woźniak, Justyna; Kopczyńska Ewelina; Kulej, Piotr; Biesiada, Wiktor; Kmieć Justyna Weronika; Chernysh, Anna-Mariia; Dusińska Aleksandra; Waszczyński Jakub; Fuczyło, Kamila; Stankevič Karolina (Quality in Sport, 2025)
Introduction Zinc plays a vital role in immune function, enhancing defense mechanisms and reducing infection duration and severity. Purpose of Research: This study aimed to assess the impact of zinc on immune function, its role in preventing and treating infections, particularly in vulnerable populations such as the elderly, and its interactions with vitamins D and C. Additionally, the research explored zinc’s effects on microbial cell membranes, gut microbiome balance, and immune modulation, focusing on age-related immune decline and infection susceptibility. Materials and Methods: The study utilized a comprehensive approach, combining literature reviews, clinical trials, experimental studies, and microbiota analyses to investigate zinc’s role in immune function, infection management, and antimicrobial resistance. Results: Zinc was found to modulate the immune system, influencing T lymphocytes, B lymphocytes, macrophages, and natural killer cells. Deficiency weakened immune responses, increasing infection risk. Zinc supplementation, especially with vitamins D and C, improved immune function, shortened infection duration, and alleviated symptoms. Zinc and vitamin D enhanced antimicrobial peptide production and epithelial barrier function, while zinc and vitamin C reduced oxidative stress and enhanced neutrophil activity. Zinc also destabilized microbial membranes, inhibiting bacterial and viral replication, including multi-drug-resistant strains. Furthermore, zinc supplementation improved gut microbiome composition, promoting beneficial bacteria and reducing pathogenic growth. Clinical studies confirmed its effectiveness in reducing respiratory infections, improving vaccine responses, and decreasing complications in vulnerable individuals.